Representation of Iconicity in Cross-Generational Poetry: A Study of Peirce's Semiotics in Poetry Collections Masih Ingatkah Kau Jalan Pulang? - Restu Kurniawan; Ali Nuke Affandy; M. Ridlwan (Jurnal Sastra Indonesia, 2026)
The background of this research is the phenomenon of literary works that continue to develop within society and have even become an important part of it. For this reason, literary works need to be approached, understood, and treated appropriately, of course, with various approaches. The focus of this research includes: the forms of signs in the form of icons, indices, and symbols that are seen in each poem in the poetry collection Masih Ingatkah Kau Jalan Pulang? by Sapardi Djoko Damono and Rintik Sedu, through Charles Sanders Peirce’s Semiotics theory, then observing the Triadic relationship between Representamen, Interpretant, and Object in the form of signs in each poem in the poetry collection Masih Ingatkah Kau Jalan Pulang? by Sapardi Djoko Damono and Rintik Sedu. The purpose of this study is to describe the forms of signs in the form of icons, indices, and symbols that are visible and to describe the triadic relationship between the representative, interpreter, and object in the form of signs in each poem in the poetry collection Masih Ingatkah Kau Jalan Pulang? by Sapardi Djoko Damono and Rintik Sedu. This study is a qualitative descriptive study. The data used in this study is diction, which consists of words, phrases, sentences, stanzas, and lines in each poem studied. Based on research into the poetry collection Masih Ingatkah Kau Jalan Pulang? by Sapardi Djoko Damono, the iconicity consists of icons, indices, and symbols. This study also identified a triadic connection in several examples of poetry. These findings help readers of the poetry collection understand each Iconic sign presented by Sapardi Djoko Damono and Rintik Sedu as poets.